Prevalence of common diseases of broiler and layer at Gazipur district in Bangladesh - Rahman, Md Arifur; Rahman, Md Mostafijur; Moonmoon, Monalisha; Alam, Khondoker Jahengir; Islam, Md Zahirul (Asian Journal of Medical and Biological Research, 2017)
The present study was conducted to determine the prevalence of broiler and layer diseases at Gazipur sadar upazilla veterinary hospital in Bangladesh. A total of 296 either dead or sick birds were considered for the present study. Diagnosis of different diseases was made on the basis of history, owners complains, age of birds, presenting signs, clinical and necropsy examination findings. The prevalence of diseases was recorded in broiler (n=189) 63.9% and layer (n=107) 36.1%. In broiler the prevalence of Colibacillosis (33.4%) was higher followed by Omphalitis (23.8%), Infectious Bursal Disease-IBD (15.3%), Newcastle disease-ND (9.0%), mixed infection (7.4%), Gout (5.3%) and Coccidiosis (5.8%). In case of layer highest prevalence was recorded in Salmonellosis (19.6%). while other diseases were Collibacilosis (15.9%), Mycoplasmosis (12.1%), ND (10.3%), IBD (8.4), Mareks (9.3%), mixed infection (8.4%), Fowl Cholera (4.7%) and Mycotoxicosis (4.7%). The present findings will help poultry researchers and practitioner to know the present status of infectious diseases of commercial chickens in the study area and also help to establish flock based control strategy. Asian J. Med. Biol. Res. June 2017, 3(2): 290-293